2009
DOI: 10.1002/ejlt.200800135
|View full text |Cite
|
Sign up to set email alerts
|

Chemically and enzymatically catalyzed synthesis of C6–C10 alkyl benzoates

Abstract: The esterification of benzoic acid with n-hexanol, n-octanol, 2-ethyl hexanol and n-decanol was investigated in detail. An analysis of the reaction kinetics of esterification in the presence of different commercially available chemical catalysts was carried out. The effects of catalyst type and loading on the reaction rate were studied. Although the considered reaction is bimolecular, it showed a first-order behavior, and a linear dependence with respect to the catalyst concentration was observed. Hence, a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…6 Generally, enzymes used as catalysts can offer the following advantages: high enantio-and regioselectivity, 7 possible catalyst recycling, 8,9 no organic solvents needed, 10 low reaction temperatures, 11,12 replacement of potentially toxic catalysts and no protection/deprotection steps. 13 Especially peroxidases, 14 cellulases and lipases can be used in order to prepare well-defined polymeric structures. A first example of lipase catalyzed polymerization is the reaction of divinylsebacate with glycerol carried out by Kobayashi and co-workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Generally, enzymes used as catalysts can offer the following advantages: high enantio-and regioselectivity, 7 possible catalyst recycling, 8,9 no organic solvents needed, 10 low reaction temperatures, 11,12 replacement of potentially toxic catalysts and no protection/deprotection steps. 13 Especially peroxidases, 14 cellulases and lipases can be used in order to prepare well-defined polymeric structures. A first example of lipase catalyzed polymerization is the reaction of divinylsebacate with glycerol carried out by Kobayashi and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…As biocatalysts could already replace chemical catalysts in many fields, such as synthesis of acrylamide using nitrile hydratase in whole cells of Rhodococcus rhodochrous, l - tert -Leucine by leucine dehydrogenase or surfactant production by Novozym 435, research is also done with the aim of using enzymes as catalysts in polymer synthesis . Generally, enzymes used as catalysts can offer the following advantages: high enantio- and regioselectivity, possible catalyst recycling, , no organic solvents needed, low reaction temperatures, , replacement of potentially toxic catalysts and no protection/deprotection steps . Especially peroxidases, cellulases and lipases can be used in order to prepare well-defined polymeric structures.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, propargyl acetate derivatives 3a-h were prepared by acylation of propargyl alcohols 1 with acid anhydrides 2 in H 2 SO 4 (Scheme 1) [20]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Krause et al reported the esterification of benzoic acid and n-hexanol in a solventless system using several lipases, including Novozym-435, although they claimed that all tested enzymes gave negligible chemical yields. 10 We have recently reported about new reaction conditions for the esterification of benzoic acid with 1-heptanol obtaining excellent yields by using the commercially available Novozym-435 and cyclohexane as the solvent. 11 Due to a loss of catalytic activity in the esterification of benzoic acid, recycling of the immobilized lipase was not feasible for more than 4 cycles.…”
Section: Introductionmentioning
confidence: 99%